Workshops on the improvement of Perak standing orders - UiTM, Faculty of Law (Faculty of Law, 2019)
In fulfilling the call for reformation of Parliament and the State Legislative Assemblies, two lecturers from the Faculty of Law, Universiti Teknologi MARA (UiTM), Dr. Norazlina Abd Aziz and Puan Habibah Omar were invited as experts in two separate workshops for the improvement of the Standing Order of Perak State Legislative Assembly. These workshops were organised by the Perak State Legislative Assembly, Executive Council Members and Perak State Secretary Office. The first round of the workshop was conducted at the Concorde Hotel, Shah Alam, while the second-round workshop was held at Hotel Seri Malaysia, Ipoh. The workshop on the Improvement of Standing Orders of Perak State Legislative Assembly on 27- 29 January 2019 at Shah Alam brought together experienced members which comprised of the Speaker of Perak State Legislative Assembly, Deputy Speaker, Members of Parliament, State Secretaries of Perak, Selangor and Negeri Sembilan as well as language experts from Dewan Bahasa dan Pustaka. The second round of workshop which was held on 25-27 February 2019 was meant to further improve the Standing Orders of Perak’s State Legislative Assembly. In both workshop sessions, the whole of Perak Standing Orders was reviewed and improved to be laid down at the State Legislative sitting in April 2019.